Investor protection and convertible debt design - Lee, Cheng-Few; Lee, Kin-Wai; Yeo, Gillian Hian-Heng (Journal of Banking & Finance, 2009)
An important issue that firms consider when designing convertible debt is to specify security features such as conversion ratio, maturity date and call period. Following Lewis et al. [Lewis, M., Rogalski, R., Seward, J., 2003. Industry conditions, growth opportunities and market reactions to convertible debt financing decisions. Journal of Banking and Finance 27, 153–181], we employ a single measure that simultaneously considers all of these features: the expected probability (measured at issue date) that the convertible will be converted to equity at maturity. We find that firms in countries with stronger shareholder rights issue convertible debt with a higher expected probability of converting to equity. The positive association between the expected probability of conversion and shareholder rights is less pronounced in firms for which ownership structures create potentially high managerial agency costs. Specifically, in countries with stronger shareholder rights, firms with higher separation of control rights and cash flow rights tend to issue convertibles with lower probability of conversion. Furthermore, we find that large non-management block ownership strengthens the likelihood of issuing convertible debt with higher probability of conversion in countries with stronger shareholder rights. In contrast, firms in countries with stronger creditor rights issue convertibles with lower probability of conversion. We also document that the negative association between creditor rights and probability of conversion is more pronounced in firms with higher separation of control rights and cash flow rights.